2014
DOI: 10.1371/journal.pone.0092113
|View full text |Cite
|
Sign up to set email alerts
|

Ascl1 as a Novel Player in the Ptf1a Transcriptional Network for GABAergic Cell Specification in the Retina

Abstract: In contrast with the wealth of data involving bHLH and homeodomain transcription factors in retinal cell type determination, the molecular bases underlying neurotransmitter subtype specification is far less understood. Using both gain and loss of function analyses in Xenopus, we investigated the putative implication of the bHLH factor Ascl1 in this process. We found that in addition to its previously characterized proneural function, Ascl1 also contributes to the specification of the GABAergic phenotype. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…Ptf1a‐committed precursors are further specified by other transcription factors (Liu et al, ; Nakhai et al, ): Nr4a2 (orphan nuclear receptor subfamily 4, group A, member 2) is essential for GABAergic and dopaminergic amacrines; and Tfap2a (AP‐2 alpha) marks a subset of glycinergic and GABAergic amacrines. Studies in xenopus retinal progenitors have suggested that Ascl1, acting in concert with Ptf1a, is sufficient and necessary for amacrine genesis (Mazurier et al, ). We detected Ascl1, Ptf1a, and Nr4a2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ptf1a‐committed precursors are further specified by other transcription factors (Liu et al, ; Nakhai et al, ): Nr4a2 (orphan nuclear receptor subfamily 4, group A, member 2) is essential for GABAergic and dopaminergic amacrines; and Tfap2a (AP‐2 alpha) marks a subset of glycinergic and GABAergic amacrines. Studies in xenopus retinal progenitors have suggested that Ascl1, acting in concert with Ptf1a, is sufficient and necessary for amacrine genesis (Mazurier et al, ). We detected Ascl1, Ptf1a, and Nr4a2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A sizeable number of proneural bHLH transcription factors have been identified that act at different stages in the specification, differentiation and maturation of a neuron [ 1 ], but how their different roles are controlled and co-ordinated is still poorly understood. We have previously shown that two bHLH proteins are controlled by multi-site phosphorylation on serine-proline sites; Ascl1, which regulates autonomic neuron formation in Xenopus [ 41 ] and generally a GABAergic phenotype (among other roles) [ 42 ], and Neurogenin2, an inducer of primary neuron formation in the developing Xenopus embryo [ 43 ] and generally of glutamatergic neurons [ 42 ]. Multi-site phosphorylation by cdks regulates the ability of Ascl1 and Ngn2 to control the proliferation versus differentiation decision; when cells are rapidly cycling, high cdk levels suppress the ability of these proneural proteins to drive differentiation [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ascl1 is another class II bHLH transcription factor particularly associated with GABAergic and noradrenergic neurogenesis in Xenopus embryos [ 18 , 19 ], while NeuroD1 is a proneural protein acting downstream of Ngn2 in the primary neurogenesis cascade. All three factors are able to induce ectopic primary neurons when over-expressed [ 7 , 12 ].…”
Section: Resultsmentioning
confidence: 99%